Analisis Hukum Perdata terhadap Keabsahan dan Pembuktian Tanda Tangan Digital Serta Pertanggungjawaban Platform E-Wallet dalam Transaksi E-Commerce - As-Sifa Pebrianti; Ardhita Aulia Utari; Salwa Fauziyah Anwar; Shabrina Najla Ingga Jayasti (Konsensus : Jurnal Ilmu Pertahanan, Hukum dan Ilmu Komunikasi, 2025)
The rapid development of digital technology has significantly transformed financial transactions in Indonesia, particularly through the growing use of e-wallets as practical and efficient payment tools. In a country with a Muslim-majority population, ensuring that e-wallet services comply with Islamic principles—free from riba, gharar, and maysir—is essential. This study aims to analyze Indonesia’s legal politics in regulating the use of e-wallets within the Islamic financial system and to assess their alignment with sharia principles. This research employs a normative juridical method with a qualitative descriptive approach by examining laws, regulations, and fatwas related to sharia-based fintech. The findings indicate that the Indonesian regulatory framework—through the OJK, Bank Indonesia, and DSN-MUI—has attempted to harmonize policies to support sharia-compliant digital financial services. However, several challenges remain, including limited e-wallet platforms with sharia certification, low digital sharia literacy among users, and the absence of detailed technical regulations specific to sharia e-wallet operations. This study recommends strengthening regulatory guidelines, increasing public literacy, and enhancing collaboration between regulators and the fintech industry to promote the development of sharia-compliant e-wallets that are secure, innovative, and aligned with Islamic financial principles.